Prospectiva de la infraestructura logística de transporte terrestre en Colombia. (2022)
The land transportation logistics infrastructure is of utmost importance to generate the growth and economic-social development of the nation [Colombia]. The existence of roads the flexibility of commercial exchange and increased productivity at national and international level.